ANALISA OPTIMALISASI LINI PRODUKSI PENGEMASAN SUSU BUBUK TERPASANG DI PT. TIGARAKSA SATRIA, TBK. - Aditia, Denny; Sardjono, Jeddy J. (Bina Nusantara University, 2012)
The topic for analysis is the capacity of the production line in PT. TIGARAKSA SATRIA, TBK. where an increase in production capacity is necessary to meet customer demand. First the researchers studied background literature, and then determined the topics to be discussed. Furthermore, they identified and formulated the problem in detail. The researchers then conducted field observations to collect data and processed the data using capacity measurement theory, and linear programming. They then analyzed the results and determine useful conclusions and suggestions for the company. The results of the data processing, gave a total installed production capacity and the remaining available capacity. It was suggested to the company that not too much should be spent producing products of high variation due to wasted setup time. In addition, companies are advised to have a generator set with the aim of reducing the time wasted due to electricity blackouts.